FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN SARUNG TENUN IKAT LAMONGAN - Rachmad Hidayat (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
This research is done in Lamongan which located in countryside of Parengan, district of Maduran, sub-province of Lamongan. The effort that developed is sarung tenun ikat production. Target of this research is to identify requirement of consumer and know dominant factor which generate tendency of enthusiasm buy of consumer to sarung tenun ikat product. At this research, intake of sampel done by purposive and data collected through kuisioner counted 100 responden. Quisioner compiled in the form of Likert Scale and data analysed by using factor analysis. Result of research indicate that to identify attribute of quality is type of sarung tenun ikat, colour of sarung tenun ikat, accuration of jacquards of sarung tenun ikat, result of jacquards of sarung tenun ikat, materials used not easy to tear, and quality as according to price. most dominant factor is brand and quality. Which the included in quality factor and brand is 2nd attribute (color), 3rd attribute (accuration), 5th attribute (materials) and 8th (brand).